Analisis Penerapan Good Corporate Governance pada Bank Sumut KCP Syariah Multatuli - M Ridho Effendy; ridhoeffendy5@gmail.com; M Ridho Effendy (MES Bogor, 2022)
ABSTRACT Good Corporate Governance is a way ofacorporateagovernanceathataaims to make the companyarun well. This study intends to let us knowahowatoaapplyatheaprinciplesaofagood corporateagovernanceaataBankaSumut kcp syariah Multatuli, a regionally owned Islamic bank whichaisaaabranch ofatheaaNorth Sumatran bank.a This research uses the principle of a qualitative approach with aasemi-structureda interviewatechnique,atoadetermineatheasources by using a purposive sampling method. The data analysis technique used in this research is data reduction in data presentation and conclusion drawing. The results of the study show the imp-lementation of Good Corporate Governance through the principle of Tariffs, namely Transparency, Accountability, Responsibility, Independence, and Fairnes. At Bank Sumut Kcp syariah Multatuli this is already good and in accordance with the principles of Good Corporate Governance. Keywords : Good Corporate Governance,TARIF; Journal Al-Kharaj.